Taxonomic Diversity of Paradise Threadfin Polynemus paradiseus (Linnaeus, 1758) inhabiting Southern Coastal Rivers in Bangladesh - Md. Reaz Chaklader,; Muhammad Abu Bakar Siddik,; Ashfaqun Nahar, (Universiti Kebangsaan Malaysia, 2015)
The study was aimed to determine the variation in taxonomic diversity of Polynemus paradiseus based on morphometric and meristic analyses of samples collected from three coastal rivers of Bangladesh (Payra, Tentulia and Kirtonkhola). A total of 105 individuals ranging at 10-20 cm in total length (TL) and 7.91-60.64 g in body weight (BW) were sampled using Been nets and Kachal and Veshal nets. Significant differences were observed in 24 out of 25 morphometric measurements and 6 out of 10 meristic counts among the populations. In morphometric measurements, the first discriminant function (DF1) was accounted for 78.6% and the second discriminant function (DF2) was accounted for 21.4% of among groups variability, explaining 100% of total among group variability. A dendrogram based on morphometric data showed that the Tentulia and Kirtankhola populations showed high degree of overlapping and these two populations were highly different from Payra river population. The canonical graph also showed that the populations of Tentulia and Kirtankhola rivers were more closely related comparing with Payra river population for isometric condition. These findings may provide useful information for the conservation and sustainable management of this important fish.